Energy consumption of battery electric bus simulated from international driving cycles compared to real-world driving cycle in Chiang Mai - Niti Kammuang-lue; Jirawat Boonjun (Energy Reports, 2021)
The objectives of this study are to compare the energy consumption rate (ECR) of battery electric bus (BEB) simulated from international driving cycles and a real-world driving cycle in Chiang Mai (CMDC) and to define the ECR multiplier to convert the simulated ECR obtained from international driving cycles to the CMDC. Four international driving cycles were chosen. Each driving cycle was separately considered for two cases, one with air resistance and one without. It was concluded that the ECR obtained from the EPA heavy duty urban dynamometer driving schedule (EPA HDUDDS) is most similar to the CMDC but the ECR obtained from the regulation of the worldwide harmonized light vehicles test procedure (WLTP) differs the most. The ECR multipliers used for correcting the simulated ECR were in a range between 0.839 and 1.711.